The Value Relevance of Earnings and Cash Flow: Regression-Variation Approach - Dwi Fitri Puspa (Journal of Accounting and Investment, 2006)
This study is conducted to measure the value relevance of earnings and cash flows by using the regression-variation approach. Specifically, the objectives of the study are to examine whether the value relevance of accounting earnings information is higher compared to that observed in the cash flow from operations.  The number of sample is 79 companies listed in Jakarta Stock Exchange and during the sample period of 1996 to 2001. The findings indicate that earnings and cash flows from operation are value-relevant. Furthermore the findings show that the value relevance of earnings information is higher than that of cash flows information.